2015
DOI: 10.1590/s1677-5538.ibju.2015.02.18
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable perineal male sling using tissue expander as an effective treatment of post-prostatectomy urinary incontinence

Abstract: Purpose To report our intermediate experience in treating patients with severe incontinence using an adjustable perineal male sling with a tissue expander.Materials and Methods An adjustable male sling procedure was performed on 21 patients with severe incontinence. The underlying etiology of urinary incontinence was radical prostatectomy in 13 patients, open prostatectomy in 5 patients and transurethral prostate resection in 3 patients. The difference between the classical and the adjustable sling is that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In the present study, as in the study by Kowalik et al, no explantation was carried out as a result of sling erosion or other procedure‐related complications, although to a small degree, these events still occur after similar continence surgeries . This further highlights the safety of this new four‐arm sling mesh.…”
Section: Discussionsupporting
confidence: 62%
“…In the present study, as in the study by Kowalik et al, no explantation was carried out as a result of sling erosion or other procedure‐related complications, although to a small degree, these events still occur after similar continence surgeries . This further highlights the safety of this new four‐arm sling mesh.…”
Section: Discussionsupporting
confidence: 62%
“…The study by Balci et al, 39 evaluated a type of sling that did not meet the inclusion criteria. The other studies were excluded for not having reported the primary outcome of this review or having presented participants with less than 12 months of follow-up 40-48 (Table 8).…”
Section: Resultsmentioning
confidence: 99%